2019
DOI: 10.1094/pdis-06-18-0980-fe
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Disease Survey of U.S. Sunflower: Disease Trends, Research Priorities and Unanticipated Impacts

Abstract: Between 2002 and 2015, a comprehensive survey of sunflower fields across seven Midwestern U.S. states was conducted 12 times and continues to be conducted every other year. The surveyors collected data on yield, agronomic management factors, disease, insect, weed, and bird damage. All surveyors were volunteers and came from universities (extension and research staff), USDA-ARS, and seed and chemical companies. In the 12 years the survey was conducted, data from 2,267 fields were collected. The results are pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
39
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 16 publications
0
39
0
2
Order By: Relevance
“…In the soil, it survives as sclerotia where it can live for up to 7 yr. The pathogen causes three yield‐limiting diseases in sunflower: wilt and basal stalk rot, mid‐stalk rot, and HR (Gulya et al, 2019). The scale of the disease problem in susceptible crops led to the formation of the USDA‐led National Sclerotinia Initiative, which has invested in the development of resistant cultivars of many crops, including sunflower, as part of a research strategy to limit the effects of Sclerotinia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the soil, it survives as sclerotia where it can live for up to 7 yr. The pathogen causes three yield‐limiting diseases in sunflower: wilt and basal stalk rot, mid‐stalk rot, and HR (Gulya et al, 2019). The scale of the disease problem in susceptible crops led to the formation of the USDA‐led National Sclerotinia Initiative, which has invested in the development of resistant cultivars of many crops, including sunflower, as part of a research strategy to limit the effects of Sclerotinia.…”
mentioning
confidence: 99%
“…Symptoms start on leaves and spread to the stalk, where tan to brown color lesions form (Talukder et al, 2014). Gulya and colleagues (2019) conducted a disease survey for US sunflower growing regions: North Dakota and Minnesota, South Dakota, Central High Plains, and Texas (TX). Mean incidence of PSC increased from 5 to 7% in Texas, 15 to 35% in the Central High Plains, 16 to 50% in South Dakota, and 25 to 56% in North Dakota and Minnesota from the first 6 yr (2002–2008) to the last 6 yr (2009–2015) of the survey.…”
mentioning
confidence: 99%
“…DeBary) and Phomopsis stem canker (caused by Diaporthe spp. Nitschke) are among the most important diseases in sunflower in North America and worldwide (Gulya et al, 2019).…”
mentioning
confidence: 99%
“…Resistance to Phomopsis stem canker is a critical trait in modern sunflower germplasm, as the disease has reduced yield worldwide since the early 2000s, particularly in the United States and Canada (Gulya et al, 2019). Phomopsis was previously thought to have been caused solely by D. helianthi (Muntanola‐Cvetkovic et al, 1981), but recent research suggests that up to 10 or more different species may cause disease in sunflower, including D. gulyae (Thompson et al, 2011), the species found to be the primary cause of Phomopsis in Australia (Mathew et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation